METHODS OF RECONSTRUCTION OF THE RECREATIONAL ZONES OF LARGE CITIES: Array - and (Municipal economy of cities. Series: «Economy science», 2018)
This article is devoted to the questions of reconstruction and recreation of recreational zones of large cities, classification of approaches in accordance with the structure of planning with natural-historical accents. Landscape parking lots within the city territories were analyzed, the main problems in the field of landscape design were identified. The analysis showed the need for a number of measures - for the reconstruction and improvement of the territory and other measures aimed at improving the existing natural areas in large cities in order to increase their recreational properties. The basic principles and methods of carrying out complex planning as one of the possible steps to improve the state of such an important element of a city-planning city as urban parks are explored. The main components of modern city parks are defined to meet the needs of all social groups. Nontraditional planning for the organization of the territory of recreational purposes, whose purpose is to constantly visit various age and social groups of the population. The state of recreation in the big cities is analyzed. The prospects for recreation and tourism development are determined by the action of a wide range of natural, historical, cultural, social, economic and political factors. Planning the development of recreational areas of large cities, based on the idea of ​​natural history, ethnographic recreation. The activities of the recreational complex provide the opportunity to heal large masses of the population and make a significant contribution to national income.An analysis of recent scientific studies shows that this topic is very relevant, this is stated in his work by the architect of the Nefedov V.A., it reveals the problems of interaction of the city and nature, also offered the theoretical basis of architectural and landscape reconstruction of park areas. Also Bobirayeva O.V. in his scientific work gives a description of recreation in the system of expanded society, and how modern society affects the development of recreational territories.At the present stage of development of park areas, the main tasks of creating, designing and rehabilitating parks in large cities are: increasing recreational attractiveness; increase of aesthetic expressiveness; creation of environmentally sustainable landscapes; self-sustainment of parks. Keywords: amelioration, methods of reconstruction, recreation zone, objects, functions, territory, multifunctional, architecture, composition, ecology, use, improvement, development.